Perancangan Aplikasi Penyisipan Pesan Teks dalam Audio dengan Menggunakan Metode Low Bit Coding - Ramadani, Muhammad (MEANS (Media Informasi Analisa dan Sistem), 2019)
The development of steganography began to penetrate into the digital world which in this study was devoted to mp3 audio files. The techniques for developing a steganography process are briefly discussed. This study also tried to present the steganography process in audio file comparisons based on the formulas in the existing literature. A software called MP3 Stego is used to assist in the process of observing problems and completing the steganography process. MP3 Stego is tried, observed, and hypothesized for future development suggestions. After looking more deeply at audio steganography, especially in MP3 audio files, it is quite prospective in the next development. Well studied from psychological and technical factors, it turns out that MP3 media is a very appropriate media to become a message hiding media. In addition, it turns out that steganography can also be used in more in-depth and broader targets such as campaign suggestions, notifications, organizational communication, and so on.